2000
DOI: 10.2307/3620769
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of racing shell oars

Abstract: By analysing the forces acting on an oar during the power stroke it is possible to estimate the mean velocity given to a racing shell. Use is made of oarlock force data, obtained experimentally by the Australian Institute of Sport, to obtain accurate predictions in the case of a racing pair. Similar conclusions would hold for boats with any number of oars. The effect of altering the angle between oar shaft and blade is investigated, leading to a suggestion for a design change to improve oar efficiency. Predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
4
0
Order By: Relevance
“…Oarlock displacement is a simple way of achieving the benefits produced by the concept of blade lead angle suggested in an earlier paper by Brearley and de Mestre [2], but without the disadvantages attending that method.…”
Section: Discussionmentioning
confidence: 99%
“…Oarlock displacement is a simple way of achieving the benefits produced by the concept of blade lead angle suggested in an earlier paper by Brearley and de Mestre [2], but without the disadvantages attending that method.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is a study by Brearley and de Mestre (2000), who found considerable increases in efficiency when the blade is tilted forward with respect to the shaft. This would offset any negative effects caused by oar bending in the mid-part of the stroke (Brearly & de Mestre, 2000). A possible problem with simulation studies like these is that it is assumed that the force input (delivered by the rower) is the same for each situation and as such independent of oar design.…”
Section: Oar Deformation Neglectedmentioning
confidence: 96%
“…Although this assumption is unrealistic, as is plainly obvious to anyone observing the deflection of an oar being rowed, it is made because little is known about either the nature of the bending, in particular the interrelation between the oar bending force and the effect of the bending on the blade forces, or the importance of including it when modelling the stroke [6]. While estimates of oar bending have been calculated using the measured oar force at the oarlock [7], a detailed quantitative analysis of bending behaviour has not yet been performed. Here, the effects of oar bending are calculated by resolving the complex time-varying hydrodynamic load on the oar blade during the drive by using a computational fluid dynamics (CFD) model.…”
Section: Introductionmentioning
confidence: 99%